2013
DOI: 10.1021/jm301519z
|View full text |Cite
|
Sign up to set email alerts
|

Novel P2 Tris-tetrahydrofuran Group in Antiviral Compound1(GRL-0519) Fills the S2 Binding Pocket of Selected Mutants of HIV-1 Protease

Abstract: GRL-0519 (1) is a potent antiviral inhibitor of HIV-1 protease (PR) possessing tris-tetrahydrofuran (tris-THF) at P2. The high resolution X-ray crystal structures of inhibitor 1 in complexes with single substitution mutants PRR8Q, PRD30N, PRI50V, PRI54M, and PRV82A were analyzed in relation to kinetic data. The smaller valine side chain in PRI50V eliminated hydrophobic interactions with inhibitor and the other subunit consistent with 60-fold worse inhibition. Asn30 in PRD30N showed altered interactions with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Coordinating these residues at the subunit–subunit interface will tend to stabilize the dimer [57]. These interactions of the inhibitor were maintained in the crystal structures of proteases bearing single substitutions of R8Q, D30N, I50V, I54M and V82A [59]. The loss of hydrophobic interactions with protease containing I50V mutation was consistent with 60-fold worse inhibition of catalytic activity, suggesting this mutation will cause resistance to the GRL-0519 inhibitor.…”
Section: Investigational Antiviral Inhibitorsmentioning
confidence: 97%
“…Coordinating these residues at the subunit–subunit interface will tend to stabilize the dimer [57]. These interactions of the inhibitor were maintained in the crystal structures of proteases bearing single substitutions of R8Q, D30N, I50V, I54M and V82A [59]. The loss of hydrophobic interactions with protease containing I50V mutation was consistent with 60-fold worse inhibition of catalytic activity, suggesting this mutation will cause resistance to the GRL-0519 inhibitor.…”
Section: Investigational Antiviral Inhibitorsmentioning
confidence: 97%
“…20 Studies of PR with single mutations, however, suggested 3 would be less effective on variants with the I50V mutation. 31 Superposition of the PR20/ 3 complex with the wild type PR/ 3 (3OK9) dimer gave a significant RMSD of 1.0 Å for 198 equivalent Cα atoms. Overall, the PR20/ 3 complex is very similar to the PR20/amprenavir and PR20/ 2 complexes and can be superimposed with lower RMSD values of 0.31 and 0.56 Å, respectively, for all Cα atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitor 2 has shown analytical purity >99% by HPLC analysis, 28 and inhibitor 3 has shown analytical purity of >98% by HPLC 31 . The structures were confirmed by 1 H and 13 C NMR spectral analysis, and high resolution mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…An X-ray structure of inhibitor 3 -bound HIV-1 protease revealed that the ring oxygens of both A and B rings of tris-THF formed strong hydrogen bonds with the backbone atoms of Asp29 and Asp30 similar to darunavir. 12 However, the C-ring oxygen did not form any direct hydrogen bonds in the active site. Instead, it formed a water-mediated hydrogen bond with the side chain of Arg8′ in the active site.…”
Section: Introductionmentioning
confidence: 96%